Differential Striatal Axonal Arborizations of the Intratelencephalic and Pyramidal-Tract Neurons: Analysis of the Data in the MouseLight Database - Morita, Kenji; Im, Sanghun; Kawaguchi, Yasuo (Frontiers in Neural Circuits, 2019)
(We would like to switch this article to a regular original research article if the editor thinks it appropriate, as we wrote in our comments to the editor)